The Collum angle of the maxillary central incisors in patients with different types of malocclusion - Yen-Wen Shen; Jui-Ting Hsu; Yi-Hui Wang; Heng-Li Huang; Lih-Jyh Fuh (Elsevier, 2012)
Background/purpose: The Collum angle (the supplementary angle of the crown-root angle) of the maxillary central incisors is extremely important for patients who are undergoing orthodontic treatment and who are to receive an implant restoration. However, there is no report on the Collum angle in Taiwanese. Therefore, the purpose of this study was to evaluate the Collum angle of the maxillary central incisors in Taiwanese patients with different types of malocclusion. Materials and methods: This study collected 124 samples of lateral cephalometric radiographs (38 radiographs from male patients and 86 from female patients). The age of sampled patients ranged 8-58 (mean, 19.9) years. Samples were divided into four groups according to the malocclusion type, and the Collum angle of the maxillary central incisors in each group was measured. A one-way ANOVA and the Scheffe test were used to compare whether or not the angle differed among the groups. Results: The average value of the Collum angle was 6.1° ± 5.2° for class-I malocclusions, 5.3° ± 4.2° for class-II division-I malocclusions, 10.6° ± 4.4° for class-II division-2 malocclusions, and 5.6° ± 5.1° for class-III malocclusions. A statistical analysis showed that the Collum angle of the maxillary central incisors for patients with class-II division-2 malocclusions significantly exceeded values in the other three groups. Conclusion: Compared to groups with other malocclusion types, the Collum angle of natural teeth for patients with class-II division-2 malocclusions was the greatest.